2016
DOI: 10.1038/srep34445
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol suppresses NTHi-induced inflammation via up-regulation of the negative regulator MyD88 short

Abstract: Upper respiratory tract inflammatory diseases such as asthma and chronic obstructive pulmonary diseases (COPD) affect more than one-half billion people globally and are characterized by chronic inflammation that is often exacerbated by respiratory pathogens such as nontypeable Haemophilus influenzae (NTHi). The increasing numbers of antibiotic-resistant bacterial strains and the limited success of currently available pharmaceuticals used to manage the symptoms of these diseases present an urgent need for the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 41 publications
0
26
0
2
Order By: Relevance
“…In a separate study, treatment with resveratrol reduced the expression of proinflammatory cytokines (IL-17, IL-6, TNF-α, and TGF-β) in the bronchoalveolar lavage fluid (BALF) of mice exposed to cigarette smoke. Along with this, resveratrol treatment also attenuated the cigarette smokeinduced fibrotic response and mucus hypersecretion in the lungs (Andrews et al, 2016). A recent study in rats also confirmed the efficacy of resveratrol in COPD, and that the beneficial effect of resveratrol may be exerted via the SIRT1 and PGC-1α axis (Wang, Li, Li, Miao, & Xiao, 2017).…”
Section: Targeting Oxidative Stressmentioning
confidence: 73%
See 1 more Smart Citation
“…In a separate study, treatment with resveratrol reduced the expression of proinflammatory cytokines (IL-17, IL-6, TNF-α, and TGF-β) in the bronchoalveolar lavage fluid (BALF) of mice exposed to cigarette smoke. Along with this, resveratrol treatment also attenuated the cigarette smokeinduced fibrotic response and mucus hypersecretion in the lungs (Andrews et al, 2016). A recent study in rats also confirmed the efficacy of resveratrol in COPD, and that the beneficial effect of resveratrol may be exerted via the SIRT1 and PGC-1α axis (Wang, Li, Li, Miao, & Xiao, 2017).…”
Section: Targeting Oxidative Stressmentioning
confidence: 73%
“…The beneficial effects of resveratrol appear to be AMPKdependent, as mice deficient of this metabolic sensor are no longer protected from metabolic derangement induced by high fat feeding despite the administration of resveratrol (Um et al, 2010). In the context of COPD, resveratrol administration to mice has been shown to alleviate Haemophilus influenzae-induced inflammation of the airway by upregulating the negative regulator of inflammation MyD88 short (MyD88s) (Andrews, Matsuyama, Lee, & Li, 2016). In a separate study, treatment with resveratrol reduced the expression of proinflammatory cytokines (IL-17, IL-6, TNF-α, and TGF-β) in the bronchoalveolar lavage fluid (BALF) of mice exposed to cigarette smoke.…”
Section: Targeting Oxidative Stressmentioning
confidence: 99%
“…Western blot procedures were previously described [2][3][4][12][13][14][15][16][17]. Western blots were performed using whole-cell extracts, separated on 8-10 % SDS-PAGE gels, and transferred to polyvinylidene difluoride we hypothesized that RIP-2 may play a critical role in regulating mucin production [22].…”
Section: Western Blotmentioning
confidence: 99%
“…NTHi were grown as previously described [12][13][14][15][16]. For in vitro experiments, NTHi was resuspended in PBS and used at a multiplicity of infection (MOI) of 50.…”
Section: Bacterial Strains and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation